Kebahagiaan Orang Percaya: Refleksi Teologis Matius 5:1-12 - Baskita Ginting (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2018)
Everybody is looking for and the pursuit of happiness in life. In a naked eyes and to the size of the general public, who gets happy is a man who has what it takes and fulfilled what is desirable. Seeking happiness tends to focus on wealth, position, and sex. As a result not a few people, from the intellectuals and layman trapped, in order to achieve such happiness. Such happiness is false. To explain happiness in accordance with Bible teaching, this study used descriptive qualitative method by analyzing the text of the Bible Matthew 5: 1-12. Based on the facts and results of text analysis, qualitative research is used to build conclusions about the importance of obtaining happiness in God through books explaining the key points in Matthew 5: 1-12. This study concludes that true happiness is the happiness that begins with the personal recognition of God, so willing to do what God says, despite the temporary suffering.AbstrakSemua orang mencari dan mengejar kebahagiaan dalam hidup ini.  Secara kasat mata dan menjadi ukuran masyarakat umum, yang berbahagia adalah orang yang memiliki apa yang diperlukan dan terpenuhi apa yang diinginkan. Kecendrungannya berfokus pada harta, tahta dan sex. Akibatnya tidak sedikit orang, dari golongan cendikia dan awam terjebak, demi mencapai kebahagiaan tersebut. Kebahagiaan demikian adalah semu. Untuk menjelaskan tentang kebahagiaan sesuai dengan pengajaran Alkitab, penelitian ini menggunakan metode deskriptif kualitatif dengan menganalisis teks Alkitab Matius 5:1-12. Berdasarkan fakta dan hasil analisa teks, penelitian kualitatif digunakan untuk membangun kesimpulan tentang pentingnya mendapatkan kebahagiaan di dalam Tuhan melalui buku-buku yang menjelaskan pokok-pokok penting dalam Matius 5:1-12. Kajian ini menyimpulkan bahwa kebahagiaan yang sejati, adalah kebahagian yang diawali dari pengenalan akan Tuhan secara pribadi, sehingga rela melakukan apa yang Tuhan firmankan, walaupun menghadapi penderitaan sementara.